Methods and Means of Training Object-Oriented Programming in Higher Education Institutions - Koniukhov, Serhii (Ukrainian journal of educational studies and information technology, 2018)
The article analyzes the methods and means of teaching that are used in the practice of training future engineer-programmers, the methods of their use in the process of formation of students competence in the field of object-oriented development. For example, the use of electronic teaching aids, taking into account the individual educational needs of students. These can be environments that implement the method of visualizing the concepts of OOP, simulators, with which you can organize an independent training with automatic checking of results, etc. Another approach is to consistently enhance the role of interactive learning methods that encourage students to independently formulate conclusions, apply existing knowledge and find new ones. The directions of further research, which consist in the development of a system of methods and teaching methods, adapted to the features of object-oriented programming as a subject of study in institutions of higher education, are determined.